Expression of P53, PTEN and S100A4 in invasive ductal breast cancer and the clinical significance - Gang, Z; Zhong, L; Xiao-meng, L; Jun-hua, Z; Yong, C; Xing, Z (Journal of Chitwan Medical College, 2017)
Objective: To investigate the expression level of P53, PTEN and S100A4 in invasive ductal breast cancer and the clinical significance. Methods: SP immunohistochemical and Western blot analysis were used to detect the expression of P53, PTEN and S100A4 protein in invasive ductal breast cancer, adjacent tissues and benign breast lesions. Results: Immunohistochemical results showed that the positive rates of P53 and S100A4 in invasive ductal breast cancer were 47.69% and 56.92%, which were significantly higher than that in benign breast lesions 16.00% and 22.00% respectively (P<0.05） while positive rates of PTEN in invasive ductal breast cancer was 24.62%, compared to benign breast lesions 52.00%（P<0.05). The expression of P53 was negatively correlated with PTEN in invasive ductal breast cancer（P<0.05). Western blot revealed that the relative expression levels of P53, PTEN and S100A4 protein in invasive ductal breast cancer were 0.967±0.066, 0.785±0.044 and 1.065±0.073 respectively, which were significantly different with that in benign breast lesions （0.549±0.032, 1.245±0.059, 0.370±0.065）（P<0.05). The expression of P53 can be correlated with histological grading and lymph node metastasis（P<0.05), but not with tumour size and clinical grade (P>0.05) While expression of S100A4 has correlation with clinical grade and lymph node metastasis（P<0.05), but no association with the age, tumour size and histological differentiating degree was observed（P>0.05). Similarly, expressions of PTEN has relation with lymph node metastasis (P<0.05), but not with the age, tumor size, clinical grade and histological grading was noted in our study（P>0.05). Conclusion: Expression of P53, PTEN and S100A4 can be taken as to the prognosis biomarkers of breast cancer and potential targets for new and effective treatment strategies for breast cancer.